NURSING CARE FOR PATIENTS VICTIM OF ACUTE MYOCARDIAL INFARCTION: A HOLISTIC VIEW - da Silva Fonseca Lima, Gabriely (Health and Society, 2023)
INTRODUCTION: Acute Myocardial Infarction (AMI) is characterized by reduced oxygen supply to the affected site, due to decreased blood flow in the coronary arteries, with consequent myocardial necrosis. OBJECTIVES: To analyze, through a literature review, the importance of nursing care for patients suffering from AMI and the relationship between the complexity of care provided and the duration of nursing care. MATERIALS AND METHODS: Refers to a literature review study focusing on Acute Myocardial Infarction, identifying the care and nursing care time required to care for clients affected by the disease. RESULTS AND DISCUSSION: For the planning and implementation of nursing care for patients diagnosed with AMI, one of the studies took into account the following complaints from female clients admitted to the ICU: Chest pain, cramps, headache with difficulties in falling asleep and incisional pain due to pericardial effusion drainage, tachycardia, nausea, cold and pale skin, hypotension, hypoactivity, bradycardia with irregular heart rate, slow response to verbal commands, in addition to anxiety. CONCLUSION: This integrative review study showed that AMI is a serious public health problem due to its high morbidity and mortality in Brazil.